2020
DOI: 10.1159/000505964
|View full text |Cite
|
Sign up to set email alerts
|

Child with Guillain-Barré Syndrome Responding to Plasmapheresis: A Case Report

Abstract: Intravenous immunoglobulin (IVIG) has long been regarded as the first-line treatment for Guillain-Barré syndrome (GBS), with plasmapheresis only being reserved for severe cases or used as an additional therapy of unproven efficacy. Here, we present the case of a 9-year-old girl with acute motor axonal neuropathy (AMAN), a rapidly progressive subtype of GBS that caused her to fall into respiratory failure. The patient failed to show a response 10 days after starting IVIG, but showed rather quick improvement wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
2
1
Order By: Relevance
“…This contrasts with some studies reporting higher percentages (above 75%) in pediatric patients early in the disease course [1,33,35,39]. Other studies suggest that normal CSF results may be observed within one week after symptoms onset [2,3,6,8], which may explain the results in our study. This warrants further investigations for future work to determine the optimal timing for diagnostically informative CSF analysis, at which it would serve as a good diagnostic test for GBS.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This contrasts with some studies reporting higher percentages (above 75%) in pediatric patients early in the disease course [1,33,35,39]. Other studies suggest that normal CSF results may be observed within one week after symptoms onset [2,3,6,8], which may explain the results in our study. This warrants further investigations for future work to determine the optimal timing for diagnostically informative CSF analysis, at which it would serve as a good diagnostic test for GBS.…”
Section: Discussioncontrasting
confidence: 99%
“…Notably, TPE has demonstrated effectiveness comparable to, or even surpassing, IVIG, while also proving to be more cost effective. This assertion aligns with őndings reported from numerous previous case series and cohort studies [2,10,28,29,33,34]. This retrospective study investigates and delves into the efficacy and safety of TPE in the management of GBS in pediatric patients, with the objective of providing valuable insights for potential inclusion in future larger-scale trials.…”
Section: Discussionsupporting
confidence: 83%
“…The main aim of the present article is to report the efficacy of TPE in a severe and rapidly progressive AMAN subtype of GBS. Another recently published case report showed the beneficial effect of TPE after IVIg failed to improve the neurological condition of a child diagnosed with the AMAN subtype of GBS (59). Cases such as this may be included in retrospective studies on the efficacy of different treatments for the axonal forms of GBS.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 This syndrome often responds to immunoglobulin when administered intravenously. 24 Myalgia/fatigue is often seen, and raised creatine kinase levels point to injury of muscle. 25 Most of the neurological complications are currently reported from the Chinese population.…”
Section: Introductionmentioning
confidence: 99%